(cosz-cos2)^{2}+(sinz-sin2)^{2} упростить выражение

0 голосов
59 просмотров

(cosz-cos2)^{2}+(sinz-sin2)^{2}

упростить выражение


Алгебра (32 баллов) | 59 просмотров
Дано ответов: 2
0 голосов

(cosz^2-2coszcos2+cos2^2+sinz^2-2sinzsin2+sin2^2)=-2(coszcos2+sinzsin2)+2

(104 баллов)
0 голосов

image

2-2(coszcos2+sin2sinz)=2-2cos(z-2)= 2(1-cos(z-2))=

2(cos0-cos(z-2))=4sin^2(z/2-1)" alt="cos^2z-2coszcos2+cos^22+sin^22-2sin2sinz+sin^2z=

2-2(coszcos2+sin2sinz)=2-2cos(z-2)= 2(1-cos(z-2))=

2(cos0-cos(z-2))=4sin^2(z/2-1)" align="absmiddle" class="latex-formula">

по-моему так,проверьте

(3.0k баллов)